Performance of clinical signs and symptoms, rapid and reference laboratory diagnostic tests for diagnosis of human African trypanosomiasis by passive screening in Guinea: a prospective diagnostic accuracy study - Camara, O.; Camara, M.; Falzon, Laura C.; Ilboudo, H.; Kaboré, J.; Compaoré, C.F.A.; Fèvre, Eric M.; Büscher, Philippe; Bucheton, B.; Lejon, V. (Springer, 2023)
Background Passive diagnosis of human African trypanosomiasis (HAT) at the health facility level is a major component of HAT control in Guinea. We examined which clinical signs and symptoms are associated with HAT, and assessed the performance of selected clinical presentations, of rapid diagnostic tests (RDT), and of reference laboratory tests on dried blood spots (DBS) for diagnosing HAT in Guinea.